Use of email, cell phone and text message between patients and primary-care physicians: cross-sectional study in a French-speaking part of Switzerland. Issue 1 (December 2016) - Dash, Jonathan; Haller, Dagmar; Sommer, Johanna; Junod Perron, Noelle
Abstract Background Physicians' daily work is increasingly affected by the use of emails, text messages and cell phone calls with their patients. The aim of this study was to describe their use between primary-care physicians and patients in a French-speaking part of Switzerland. Methods A cross-sectional mail survey was conducted among all primary-care physicians of Geneva canton (n  = 636). The questionnaire focused on the frequency of giving access to, type of use, advantages and disadvantages of email, cell phone calls and text messages communication between physicians and patients. Results Six hundred thirty-six questionnaires were mailed, 412 (65 %) were returned and 372 (58 %) could be analysed (37 refusals and three blanks). Seventy-two percent physicians gave their email-address and 74 % their cell phone number to their patients. Emails were used to respond to patients' questions (82 %) and change appointments (72 %) while cell phone calls and text messages were used to follow patients' health conditions. Sixty-four percent of those who used email communication never discussed the rules for email exchanges, and 54 % did not address confidentiality issues with their patients. Most commonly identified advantages of emails, cell phone calls and text messages were improved relationship with the patient, saving time (for emails) and improving the follow-up (for cell phone and text messages). The main disadvantages included misuse by the patient, interference with private life and lack of reimbursement. Conclusions These tools are widely used by primary-care physicians with their patients. More attention should be paid to confidentiality, documentation and reimbursement when using email communication in order to optimize its use.